Gender-responsive climate information services in agrifood systems - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2024)
Climate variability and extreme weather events pose significant threats to agrifood systems worldwide. Thus, reliable and timely climate information services (CIS) are critical for farmers to make informed decisions, mitigate risks and adapt to climate change. Effective CIS can enhance resilience, support climate change mitigation and adaptation efforts and improve livelihoods. While women are known to be disproportionately vulnerable to climate change, they are often excluded or lack access to these essential services due to persistent structural inequalities and social barriers. The CGIAR GENDER Impact Platform is just completing a mapping of CIS provision in Low- and Middle-Income Countries (LMICs) and a scoping review to investigate gendered access to and usability of climate information in agrifood systems. The review reveals significant gaps in CIS provision, highlighting the need for gender-responsive approaches. The emerging findings highlight the importance of addressing the unique needs and challeng